2007
DOI: 10.1073/pnas.0702813104
|View full text |Cite
|
Sign up to set email alerts
|

Multitrophic interaction facilitates parasite–host relationship between an invasive beetle and the honey bee

Abstract: Colony defense by honey bees, Apis mellifera, is associated with stinging and mass attack, fueled by the release of alarm pheromones. Thus, alarm pheromones are critically important to survival of honey bee colonies. Here we report that in the parasitic relationship between the European honey bee and the small hive beetle, Aethina tumida, the honey bee's alarm pheromones serve a negative function because they are potent attractants for the beetle. Furthermore, we discovered that the beetles from both Africa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
86
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 19 publications
2
86
0
Order By: Relevance
“…The strong bouquet of a whole colony might not enable any quantitative discrimination by SHB. Furthermore, fermentation products of beetle-associated yeast are attractive to SHB and might cause aggregations (Torto et al, 2007). However, it remains to be shown to which extent fermentation actually takes place in SHB infested but otherwise healthy colonies, especially in the absence of feeding SHB larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong bouquet of a whole colony might not enable any quantitative discrimination by SHB. Furthermore, fermentation products of beetle-associated yeast are attractive to SHB and might cause aggregations (Torto et al, 2007). However, it remains to be shown to which extent fermentation actually takes place in SHB infested but otherwise healthy colonies, especially in the absence of feeding SHB larvae.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome host defence, SHB might use a mass attack strategy as is known in Scolytidae, such as the bark or pine beetles (Person, 1931;Thalenhorst, 1958), by using pheromones or invading as swarms (Tribe, 2000). However, despite intensive research, such pheromones have not yet been identified (Torto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Potent volatile organic compounds produced by this bacterium are more attractive to worms than those from ordinary dietary bacteria, luring the nematode and permitting successful infection. Among volatile organic compounds, 2-heptanone belonging to methyl ketone, a compound found widely in nature, has been reported to serve as a biological pheromone in some species (15). Our previous work has revealed an interesting phenomenon: the fatal pathogenic bacterium B. nematocida 16 can imitate this beneficial signal to trap animals.…”
mentioning
confidence: 99%
“…As such, the collection, analyses, bioactivity of identified honey bee odours is vital to understanding how social cohesion is maintained, regulated and influenced by various biotic factors such as foreign intruders (Torto et al, 2005(Torto et al, , 2007a(Torto et al, , 2007b and pathogens (Swanson et al, 2009). Odours associated with honey bees have been used to improve colony vigour and to manage certain pest such as the small hive beetle Aethina tumida, (Teal et al, 2006;Arbogast et al, 2007;Torto et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…A specialized method that provides information on honey bee detection and sensitivity to specific compounds is coupled Gas Chromatography-ElectroAntennographic Detection (GC-EAD) (Schneider, 1957;Baker et al, 1985;Torto et al, 2007a;Swanson et al, 2009). This coupled system uses an insect antenna in tandem with a flame ionization detector (FID) This section focuses on methods to collect honey bee odours outside of the colony environment (ex-situ volatile collection) and to carry out electrophysiological recordings using antenna or other chemosensory body parts of the honey bee.…”
Section: Introductionmentioning
confidence: 99%